Prevalence of high serum uric acid is increased in ambulatory subjects with hyperglycemia and dyslipidemia - Rosa, Tânia Torres (2010)
INTRODUCTION: Serum uric acid has been considered a marker or an element of the clinical and laboratory alterations in the metabolic syndrome. OBJECTIVE: to evaluate the association between levels of serum uric acid (UA) and the following laboratory profile: fasting glucose > 100 mg/dl, triglycerides > 150 mg/dl and high density lipoprotein cholesterol (HDL-C) < 50 mg/dl in women and < 40 mg/dl in men. METHOD: In a cross-sectional survey, blood samples of 4,328 randomized outpatients aged from 20 to 102 years were analyzed. RESULTS: The mean (interquartile range) UA level was higher in men (6.7; 2.4-12.5 mg/dl) and women (5.4; 2.0-12.2 mg/dl) with the laboratorial profile than in those without it (5.9; 0.90-33.8 mg/dl for men and 4.4; 0.8-30.0 mg/dl for women) (p < 0.0001). A significant increase in the prevalence of laboratory profile was observed in men (OR = 2.2 mg/dl; 95% CI: 1.2-3.9 mg/dl) and women (OR = 2.2 mg/dl; 95% CI: 1.4-3.5 mg/dl) with hyperuricemia. CONCLUSION: These results show the association between serum levels of uric acid and metabolic syndrome profile, which corroborates to similar results found in other populations worldwide.